2022
DOI: 10.1681/asn.2021111488
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplant-Membranous Nephropathy Is Associated with Protocadherin FAT1

Abstract: Background: Membranous nephropathy (MN) is a common cause of proteinuria in patients receiving a hematopoietic stem cell transplant (HSCT). The target antigen in HSCT-associated MN is unknown. Methods: We performed laser microdissection and tandem mass spectrometry (MS/MS) of glomeruli of 250 cases of PLA2R-negative MN to detect novel antigens in MN. This was followed by immunohistochemical (IHC)/immunofluorescence microscopy (IF) studies to localize the novel antigen. Western blot analyses were performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…NELL-1 associated membranous GN following HSCT has also been described 92 . A study published by Sethi et al 93 revealed a novel protein, protocadherin (FAT1), which was detected by microdissection and mass spectrometry in patients with HSCT-associated membranous nephropathy, all of whom were PLA2R antigen negative. The FAT cadherins comprise four members, FAT1-FAT4, and all are large transmembrane proteins of 500-600 kD 94 .…”
Section: Novel Antigens Associated With Hsct Associated Nephrotic Syn...mentioning
confidence: 99%
“…NELL-1 associated membranous GN following HSCT has also been described 92 . A study published by Sethi et al 93 revealed a novel protein, protocadherin (FAT1), which was detected by microdissection and mass spectrometry in patients with HSCT-associated membranous nephropathy, all of whom were PLA2R antigen negative. The FAT cadherins comprise four members, FAT1-FAT4, and all are large transmembrane proteins of 500-600 kD 94 .…”
Section: Novel Antigens Associated With Hsct Associated Nephrotic Syn...mentioning
confidence: 99%
“…Laser microdissection and mass spectrometry on kidney biopsies of PLA2R-negative PMN has led to the discovery of many more disease antigens such as NELL1, Sema3B, protocadherin 7 (PCDH7), high temperature requirement A serine peptidase 1 (HTRA1), and netrin G1 (NTNG1) ( Figure 1B.3 ). These antigens account for less than 10% of PMN and their associated autoantibodies vary in their predominant IgG subclass, ability to activate complement, and the association of their pathogenic epitope with disulfide bonds based on whether autoantibodies were detected under reducing or non-reducing conditions ( Table 1 ) ( 40 , 41 , 43 50 ). Anti-Sema3B autoantibodies correlated with disease activity in a case report of severe pediatric PMN, suggestive of pathogenicity ( 84 ).…”
Section: Antigens and Autoantibodies In Human Membranous Nephropathymentioning
confidence: 99%
“…This may be due to EXT1/EXT2-related glycosylation of heparan sulfate, which protects the GBM against immune injury. Contactin 1 (CNTN1) is associated with chronic inflammatory demyelinating polyneuropathy-related MN and protocadherin FAT1 (FAT1) is associated with allogeneic hematopoietic stem cell transplant-related MN ( 49 , 50 ).…”
Section: Antigens and Autoantibodies In Human Membranous Nephropathymentioning
confidence: 99%
“…Reports of specific antigens for MN began with the identification of M-type phospholipase A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A) . 1,2 From 2019 onwards, the success of combined laser microdissection and mass spectrometry techniques led to the discovery of various antigens including exostosin 1/exostosin 2 (EXT1/EXT2) 3 , neural epidermal growth factor-like 1 protein (NELL1) 4 , semaphorin 3B 5 , neural cell adhesion molecule 1 6 , protocadherin 7 7 , serine protease HTRA1 8 , transforming growth factor beta receptor 3 9 , protocadherin FAT1 10 , contactin 1 11 and netrin G1 12 . As of 2022, it is estimated that the complete picture of the specific antigens of MN is close to being elucidated.…”
Section: Introductionmentioning
confidence: 99%